61 Computed tomography-derived left atrial volume index, sex, and age to predict the presence and the extent of left atrial low voltage zones in patients with atrial fibrillation: the ZAQ score. (17th July 2020) - D'Ambrosio, Gabriele; Romano, Silvio; Alothman, Obaida; Frommhold, Markus; Borisov, Georgi; El Garhy, Mohammed; Issa, Karam; Penco, Maria; Raffa, Santi; Geller, Johann Christoph
Abstract : Background: Pulmonary vein isolation is the cornerstone of catheter ablation in patients with atrial fibrillation (AF). However, with advanced left atrial (LA) structural changes, additional targeted catheter ablation of low voltage zones (LVZs) has produced favorable results. Therefore, with the advent of single-shot techniques, it would be helpful to predict the presence of LVZs before an ablation procedure. Objective: We hypothesized that computed tomography-derived (CT) left atrial volume index (LAVI), in combination with other objective parameters, could be used to develop a score able to predict the presence of LVZs. Methods: In a large cohort of patients undergoing their first AF ablations, comprehensive echocardiographic evaluations and cardiac CT were performed. During the electrophysiological studies, LA geometry and electro-anatomic voltage maps were created. LVZs were defined as areas ≥1cm2 with bipolar peak-to-peak voltage amplitudes ≤0.5 mV. Results: In a derivation cohort of 374 patients, predictors of LVZs were identified by regression analysis and used to build the ZAQ score (age≥65 years, female sex and CT LAVI≥57ml/m2). The ZAQ score of 2 points accurately identified the presence and the extent of LVZs (AUC 0.809, 95% CI 0.758-0.861, p<0.001; 3 cm2 [IQR 1.5-4.5] vs 7 cm2 [IQR 4-9], p 0.001). In a validation cohort of 103 patients, the predictive value of the score was confirmed (AUC 0.793, 95% CI 0.709-0.878, p<0.001; 4 cm2 [IQR 2-7] vs 11.5 cm2 [IQR 8-16.5], p 0.001). Conclusions: The ZAQ score identifies LVZs and may be useful for planning the ablation strategy ahead of time (single shot PVI vs 3D mapping-guided ablation) regardless of whether the AF pattern is paroxysmal or persistent. Figure legend. Proposed AF ablation workflow independent of the temporal pattern of AF (ie. paroxysmal vs. persistent). (CT) Computed Tomography, (LAVI) Left Atrial Volume Index, (PVI) Pulmonary vein isolation. *Low voltage zones, if present, could be targeted with additional substrate modification ablation Conflict of Interest: None